A REPORT ON WORLD’S TOP 20 UNIVERSITIES WEBSITE MARKETING COMMUNICATION STRATEGY: WHAT CAN BE EMULATED - Chong Pei Wen; Siti Zakiah Melatu Samsi; Mohd Nazri Mohd Noor, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The university website is important as a window for potential students. Its quality is directly associated with the image and reputation of the university, reflecting the level of the university. Therefore, it is vital that a university is able to establish a website that has a high level of usability, functionality, and creativity which can attract and retain the users. In order to have a rational understanding and learning from the experienced university websites, this study has selected the top 20 universities around the world where important elements from their websites are being studied and evaluated thoroughly. The elements include picture resolution, typography, layout, web structure and colour, type of information and content as well as the privacy and trust policy. The study provides important provision on how the world-class universities designed their websites which would potentially yield refinements to the current website of other universities around the globe.